Chapter Toward a Migratory Turn - Dogramaci, Burcu (De Gruyter, 2019)
How can we think of art history as a discipline that moves process-based, performative, and cultural migratory movement to the center of its theoretical and methodical analyses? With contributions from internationally renowned experts, this manual provides answers as to what consequences the interaction of migration and globalization has on research in the field of the science of art, on curatory practice, and on artistic production and theory.